Impact of feed form and nutrient distribution in an automated commercial broiler feeding system - Hancock, Christopher J.K. (Kansas State University, 2010)
The modern poultry industry uses auger feed lines to transport feed for broilers to pans to make feed available for them while greatly reducing labor costs. The feed given to broilers is manufactured at significant cost into a pelleted form. Pellets reduce broiler production costs by increasing feed intake and growth rate while reducing feed. Pellet quality is expressed using a method called the Pellet Durability Index (PDI). A series of studies was conducted to determine the effects of these destructive forces on both pellet quality and nutritive value. In Experiment 1, it was found that pellets of 78 and 86 PDI had 30% more fines in the final pan compared to the initial pan, but there was no significant difference between the two diets. In Experiment 2, a significant difference existed between a 23 PDI diet and an 82 PDI diet in the percentage of fines found at 12 selected pans. This indicates destruction occurring along the length of the feed line. In Experiment 3, soybean oil was applied to the exterior of the pellets and they were transported through the feed line. A significant difference in the amount of fat at each collection site was found, as the fat was removed from the exterior of the pellets in earlier pans, indicating destructive forces having an effect on the pellets. In Experiment 4, whole sorghum was used to create four diets with similar PDI. The feed was then placed in the feed line, collected at twelve locations, and analyzed for crude fat, CP, DM, ash and Ca. The results indicated the presence of whole sorghum in the pellets had no effect on percent fines or nutrient values. In Experiment 5, three diets with different PDI were transported through the feed line. Five collection sites were selected. Results indicate that high quality pellets withstand handling while pellets below 68 PDI show increased fine percentage. These experiments indicate pellets are damaged during transport in the feed line, but nutrients remain the same unless they are on the exterior of the pellet.
Keywords: Pellet Quality; Poultry; Pellet; Feeding System; PDI; Agriculture, Animal Culture and Nutrition (0475); Agriculture, General (0473)